Improving associative memory in younger and older adults with unitization: evidence from meta-analysis and behavioral studies - Liu, Zejun; Wang, Yujuan; Zhu, Yajun; Yuan, Jing; Liu, Wei (Frontiers in Aging Neuroscience, 2024)
Introduction The finding that familiarity can support associative memory by unitizing the to -be-learned items into a novel representation has been widely accepted, but its effects on overall performance of associative memory and recollection are still controversial. Methods The current study aims to elucidate these discrepancies by identifying potential moderating factors through a combined approach of meta-analysis and behavioral experiment. Results Results consistently showed that changes in the level of unitization and age groups were two important moderators. Specifically, unitization enhanced younger and older adults’ associative memory and its supporting processes (i.e., familiarity and recollection) when the level of unitization between studied and rearranged pairs was changed. However, when this level remained constant, unitization exhibited no impact on associative memory and familiarity in younger adults, but showed an enhanced effect in older adults. Furthermore, results revealed a marked group difference between younger and older adults in associative memory when the unitization level of noncompound words remained unaltered. Upon breaking this condition, the group difference was reduced by enhancing familiarity or recollection. Discussion These findings not only clarify some of the inconsistencies in the literature concerning the impact of unitization on associative memory, but also suggest that unitization is a beneficial strategy for reducing group difference in associative memory, with its effectiveness varying according to the level of unitization changes.